Influence of Celebrity Athletes on the Sportswear Industry: An analysis of influencers’ impact on Nike and Adidas brand image - Sande, Artem van de, 1996- (2019)
This study aims to investigate the effects of celebrity influencers on the brand image of sportswear companies among consumers in Iceland. Using quantitative methods, data were collected through a questionnaire and later analysed, and an ANOVA test was performed when comparing the means. The results show that participants favour Nike over Adidas on four out of six associated elements: uniqueness; good price; good access to goods; use daily at school, work and/or other. Furthermore, results show that there was no significant difference between participants that experience positive nor negative effects from the influencer and the participants’ overall view on the brand image. There were a few limitations encountered during the study, including the small sample size, insignificant results, and the convenience sampling method used to collect data.